Health dynamics in camps and on campuses: stressors and coping strategies for wellbeing among labourers and students in Cameroon. Issue 1 (1st January 2018) - Makoge, Valerie; Maat, Harro; Vaandrager, Lenneke; Koelen, Maria
ABSTRACT: Purpose: For many people living in low-income countries, poverty implies an increased exposure to conditions that threaten health and wellbeing as well as reduced capacity to maintain health. Despite the challenging conditions caused by poverty, people may consider themselves healthy because they have learned to cope with their situation probably as a result of life experiences which expose people to both challenges and potential solutions. In this paper we present results from studying health and wellbeing challenges and mechanisms to cope with challenges among two different groups of people who are living under conditions of poverty: workers of the Cameroon Development Corporation (CDC) and students of the university of Buea and the university of Yaoundé. Methods: We performed a cross-sectional study, interviewing 21 CDC workers and 21 students. Results Our study reveals context-specific stressors emerging from poor work conditions and study pressure as well as non-context-specific stressors perceived by respondents as living conditions, poor healthcare and financial uncertainty. Respondents devised coping mechanisms to overcome exactly those stressors such as searching for additional money sources, preventive action towards hazardous living conditions and alternative medical support. Conclusion: We conclude that supporting and promoting such avenues is essential for enhanced and continuous coping with stressors.